STRATEGI PENGGUNAAN DIGITAL MARKETING DALAM MENINGKATKAN PENJUALAN UMKM DI PONTIANAK - Amelia Amelia; Achmadi Achmadi; Syamsuri Syamsuri (Universitas Tanjungpura, 2023)
The aim of this research is to determine the strategies and obstacles to using digital marketing in increasing MSME sales in the city of Pontianak. The approach used is in the form of qualitative case study research. Interviews and observations were conducted on 6 MSMEs in the city of Pontianak with different business fields with a total of 12 informants, namely 6 MSME actors and 6 customers. Data collection was carried out using in-depth interviews and observations as well as some documentation relevant to the research. The results of this research found that the use of digital marketing strategies implemented by MSMEs in Pontianak involves the use of social media and ecommerce platforms such as GrabFood, Gofood, Shopee Food, and Maxim. Among social media platforms, Instagram is the most commonly used. Business owners also implement auto reply digital marketing strategies to serve customers in their digital marketing and also collaborate with endorsements in promotional efforts. The increase in sales is one of the results of the strategy of using digital marketing which can be seen in the comparison between before and after the use of digital marketing, with sales income tending to increase from the start of the business or even not decreasing. In using digital marketing, business actors have several obstacles such as limited time in carrying out promotional activities such as content creation and errors in choosing endorsement services.